Análisis del comportamiento de usuarios de la tercera edad en el servicio de la salud privada en la ciudad de Machala - Espinoza Padilla, Jessica Yuliana (2015)
Taking a purchase decision involves taking into account many factors, including the costs of internal production, production capacity, the existence of qualified personnel, etc. Domestic production ensures the company or organization tight control over the whole process; however the external production allows consideration of technological advances and scientific analysis to be treated in the health services. It should be noted that an analysis of private health services, is a major social, community and corporate contribution, since by the results obtained will facilitate sound decision making in production and supply of health services of high quality and according to technological innovation, medical advances premium coverage and more satisfied patients. By analyzing the private health services offered hereby respond to questions and concerns and demands that result in allowing me own needs of users to develop adaptive offering. In considering the proposed theme was achieved develop growth strategies, advertising and loyalty through the media that disseminate high quality services according to the demands of users and advances of modern medicine. It should be noted that this project will help us identify opportunities and weaknesses to enable and encourage better training of health professionals who currently work in our city, with it's direct beneficiaries are the users that need or regularly attend a prevention health control with the goal of welfare.